Ensino/aprendizagem de línguas em teletandem: espaços para autonomia e reflexão - Garcia, Daniela Nogueira de Moraes [UNESP] (My University, 2012)
This paper focuses on teletandem telecollaborative practice aiming at maximizing the teaching and learning foreign languages and investigating the spaces created for autonomy and reflection. Teletandem is a new context for learning languages in which students are paired up and help each other to learn the language. A qualitative ethnographic study was conducted from partnerships of Brazilian and American students. Based on e-mails, informal conversations, written reports and field notes taken at the Teletandem Laboratory, the results have shown that autonomy is gradually experienced by the partners as they take responsibility for their learning. Teletandem has also proved to be a context which fosters reflective actions.

Este artigo aborda a prática telecolaborativa em teletandem visando a maximizar o ensino e a aprendizagem de línguas estrangeiras e investigar os espaços para o exercício da autonomia e reflexão. O teletandem é um novo contexto para a aprendizagem de línguas no qual parcerias são formadas por alunos que se ajudam a aprender a língua. Um estudo qualitativo de cunho etnográfico foi conduzido e enfocou parcerias entre alunos brasileiros e americanos. A partir de e-mails, conversas informais, relatórios escritos e notas de campo coletadas no Laboratório de Teletandem, os resultados apontaram que a autonomia é gradativamente vivenciada pelos parceiros ao assumirem a responsabilidade por sua aprendizagem. Verificou-se, também, que o teletandem é um contexto que fomenta atitudes reflexivas.
Teaching/learning languages in teletandem: spaces for autonomy and reflection
Keywords: Foreign Languages; Telecollaboration; Autonomy; Reflection; Línguas estrangeiras; Telecolaboração; Autonomia; Reflexão